Penitentiary and criminal inclusive public policy of discharge for the reading of literature classics - Santos, Thais Lino dos; Silva, Andre Ricardo Fonseca da (Direito e Desenvolvimento, 2019)
This article deals with a study about the efficacy of reading literature classics as a complementary educational activity in the discharge process. It is an attempt to construct public policies aimed at the re-education of the distressed student, escaping from the social imaginary dominated by punitive and repressive thinking regarding crime and violence. The practice of reading in criminal facilities deserves greater diffusion and application in the process of remission of the sentence, since it presents the maximum plausibility for an effective reeducation of the prisoner and its consequent social inclusion. We live in a world with a view to sustainability, where peace, justice, freedom, dignity, fraternity are in the process of achieving its highest level of effectiveness. It is no longer possible to perpetuate a criminal policy that has long demonstrated its inefficiency. It is through the practice of reading in criminal facilities, more specifically the reading of classics of the universal and Brazilian literature, that it is intended to defend a humanizing public policy, in opposition to the merely criminal policies that are still applied in the XXI century. The methodology used was qualitative, using the method of historical-comparative-sociological procedure and bibliographic research.